Dedifferentiated Liposarcoma of the Gastroesophageal Junction - Gökçe AŞKAN; Pelin BAĞCI; Meera HAMEED; Olca BAŞTÜRK (Federation of Turkish Pathology Societies, 2018)
Liposarcoma is one of the most common sarcomas in adults, but very rarely presents as a primary in the upper gastrointestinal system. Herein, we present a 71-year-old male patient who underwent wedge excision biopsy twice and then fine needle aspiration and total gastrectomy for a recurrent gastroeosophageal junction mass. In microscopic sections, both well-differentiated and dedifferentiated components were seen. Tumor cells were positive for MDM2, CDK4 and negative for CD117, DOG1, CD34, SMA, Desmin, S-100, HMB45, SOX10, AE1/AE3, CAM5.2, CK18. Fluorescence in situ hybridization (FISH) was performed and MDM2 gene (12q15) amplification was detected. According to these findings, a diagnosis of dedifferentiated liposarcoma was supported. We believe this is the first reported case of dedifferentiated liposarcoma of the gastroesophageal junction.